2013
DOI: 10.12691/education-1-4-2
|View full text |Cite
|
Sign up to set email alerts
|

Novice Teachers’ Challenges and Survival: Where do Malaysian ESL Teachers Stand?

Abstract: The transition from the teacher education institution to life in a real classroom has been characterized as a type of reality shock in which beginning teachers realize that the ideals they formed while training may not be appropriate for the realism they are faced with during their first year of teaching [1]. Unfortunately, this concern is not fully addressed in schools in Malaysia as beginning teachers have the same responsibility as a teacher with many years of service. It is suggested that it is not until t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 10 publications
2
37
0
4
Order By: Relevance
“…This study showed that the novice teachers' initial concerns and challenges in the first years of their teaching are similar to the early studies in the field (Farrell, 2009;Bullough et al, 1991;Senom et al, 2013;Warfood & Reeves, 2003). In the present study, the teachers' concerns are primarily related to classroom management, implementation of the communicative approach in classrooms, unmotivated students, and students with learning disabilities.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This study showed that the novice teachers' initial concerns and challenges in the first years of their teaching are similar to the early studies in the field (Farrell, 2009;Bullough et al, 1991;Senom et al, 2013;Warfood & Reeves, 2003). In the present study, the teachers' concerns are primarily related to classroom management, implementation of the communicative approach in classrooms, unmotivated students, and students with learning disabilities.…”
Section: Discussionsupporting
confidence: 74%
“…Learning about teaching is a situated process; the new teacher is socialized into a "community of practice" in which novices "move toward full participation in the sociocultural practices of a community [and gradually they] learn about the relations between newcomers and old-timers, and about activities, identities, artefacts, and communities of knowledge and practice" (Lave & Wenger, 1991, p. 29). Senom, Zakaria, and Shah (2013) investigated the challenges faced by novice English as second language (ESL) teachers in Malaysia in the early years of teaching. This nationwide large-scale study examined novice teachers' socialization experiences.…”
Section: Introductionmentioning
confidence: 99%
“…The first three years of teaching has an important impact on the future careers of novice teachers worldwide (Stokking, Leender, De Jong, & Van Tarwijk, 2003). They are not only inundated with the complexities, ambiguities and uncertainties of a teacher's work and of learning to teach but the transition from training institutions to the classrooms in schools can be characterized as a 'reality shock' (Fatiha, Abd Razak & Shanina, 2013 Instruction, January 2017 • Vol.10, No.1 Malaysia are no different. Unfortunately, the competency of a novice teacher is judged almost immediately during periods of their teaching through observations by their school principal as part of their performance evaluation before being confirmed into the teaching profession.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in several countries revealed that pre-service teachers transitioning into the profession commonly experience problems with school principals and inspectors, have heavy workloads, feel incompetent in classroom management, and have social status problems Öztürk & Yıldırım, 2013;Senom, Zakaria, & Shah, 2013;Veenman, 1984). Furthermore, research in several countries also found that the participants experience occupational concerns, perception of incompetence, and reality shock in the early years of their career (Beck, 1993;Dyess & Sherman, 2009).…”
mentioning
confidence: 99%